Minimally Invasive Periodontology: A Treatment Philosophy and Suggested Approach - Ethan Ng; John Rong Hao Tay; Marianne Meng Ann Ong (International Journal of Dentistry)
Severe periodontitis is a highly prevalent dental disease. With the advent of implant dentistry, teeth are often extracted and replaced. Periodontal surgery, where indicated, could also result in increased trauma to the patient. This literature review discusses different treatment modalities for periodontitis and proposes a treatment approach emphasizing maximum preservation of teeth while minimizing morbidity to the patient. Scientific articles were retrieved from the MEDLINE/PubMed database up to January 2021 to identify appropriate articles that addressed the objectives of this review. This was supplemented with hand searching using reference lists from relevant articles. As tooth prognostication does not have a high predictive value, a more conservative approach in extracting teeth should be abided by. This may involve repeated rounds of nonsurgical periodontal therapy, and adjuncts such as locally delivered statin gels and subantimicrobial-dose doxycycline appear to be effective. Periodontal surgery should not be carried out at an early phase in therapy as improvements in nonsurgical therapy may be observed up to 12 months from initial treatment. Periodontal surgery, where indicated, should also be minimally invasive, with periodontal regeneration being shown to be effective over 20 years of follow-up. Biomarkers provide an opportunity for early detection of disease activity and personalised treatment. Quality of life is proposed as an alternative end point to the traditional biomedical paradigm focused on the disease state and clinical outcomes. In summary, minimally invasive therapy aims to preserve health and function of the natural dentition, thus improving the quality of life for patients with periodontitis.